To Get Systems Engineers Interested in Social Dimensions, Give Them a Social Optimization Problem. Issue 3 (6th October 2021) - McDermott, Tom; Nadolski, Molly
ABSTRACT: Systems engineering provides methods and tools to model and design the engineered system jointly with the external context of the system, specifically including social, economic and policy models. This article provides an example approach to formally model the system to optimize around social constructs (recognized social variables). In an educational program, this challenges engineering students to work through an optimization problem that considers social, economic, and technical requirements and conduct trades equally across all dimensions. We present a case study on student‐led implementation trades for urban electrical microgrids that optimize community sustainability and resilience. In this case study, the students used formal models of non‐traditional socioeconomic variables such as availability, energy burden on residents, and local jobs created. The case study presents a straightforward process that considers social requirements and metrics in systems engineering design that are typically overlooked. We present this as both an example learning framework and a broader call to define and standardize systems engineering methods, processes, and tools for increased integration of social dimensions as functional requirements in future systems.